201 consecutive cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) procedures in a single Asian tertiary centre. (3rd April 2017) - Tan, Grace; Chia, Claramae; Kumar, Mrinal; Choo, Su Pin; Chia, John; Tham, Chee Kian; Chua, Clarinda; Soo, Khee Chee; Teo, Melissa
Abstract: Introduction: Peritoneal carcinomatosis (PC) is increasingly being treated with cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC). We provide a review of a high-volume Asian institute's experience and survival outcomes with this procedure. Methods: Data were prospectively collected from 201 consecutive CRS and HIPEC procedures performed in a single institution between April 2001 and November 2015. Our primary endpoints were overall survival (OS) and disease-free survival (DFS), and secondary endpoints were morbidity and mortality. Results: 77% of patients were Chinese, 9% were Malay, 6% were Indian and 8% were other ethnicities. Primary tumours were colorectal (30%), ovarian (32%), appendiceal (20%), primary peritoneal (6.5%), mesothelioma (4.5%) and others (5%). The median peritoneal cancer index (PCI) was 12, and 92% of patients achieved a completeness of cytoreduction score (CC) of 0. High-grade morbidity occurred in 25.8% of cases, and there were no 30-day mortalities. At 5-years, the OS was 55.1% and DFS was 20.3%. Factors associated with improved OS on multivariate analysis were PCI <15 ( p  < 0.001) and a CC 0 ( p  = 0.016). Conclusions: The combined treatment of CRS and HIPEC is beneficial and is associated with reasonable morbidity and mortality in Asian patients with PC from colorectal, ovarian, appendiceal, primary peritoneal and mesothelioma primaries. Complete cytoreduction and extent of disease are the most important prognostic factors for survival.